Wind speed, sun exposure and water status alter sunburn susceptibility of grape berries - Müller, Kai; Keller, Markus; Stoll, Manfred; Friedel, Matthias (Frontiers in Plant Science, 2023)
In the context of climate change, yield and quality losses from sunburn necrosis are challenging grape growers around the world. In a previous review, we identified the role of wind speed, duration of heat exposure, drought stress and adaptation as major knowledge gaps that prevent a better predictability of sunburn events. In this paper we present results of targeted experiments aiming to close these knowledge gaps. The effects of drought stress and adaptation on sunburn susceptibility were investigated in a combined drought stress/ defoliation experiment. Riesling grapevines growing in an arid climate were fully irrigated or drought stressed, and clusters were exposed to sunlight by fruit-zone leaf removal (defoliation) at two developmental stages. Sunburn symptoms were induced using infrared heaters while fruit surface temperature was measured using thermal imaging enabling the establishment of threshold temperatures. The influence of the duration of heat exposure of berries was examined by heating grape clusters to a stable temperature and monitoring the evolution of sunburn symptoms over time. To examine the effects of wind speed on the appearance of sunburn necrosis symptoms, fruit surface temperatures and sunburn severity were measured along an artificially induced wind speed gradient in two cultivars using thermal imaging and visual inspection. Longer durations of heat exposure required lower fruit surface temperatures to induce damage, while the differences in temperature after 60 min and 90 min of exposure were marginal (47.82 ± 0.25 °C and 47.06 ± 0.26 °C). Clusters of vines grown under water deficit were less susceptible to sunburn compared to those of well-irrigated plants following defoliation. The lethal temperature of clusters exposed to sunlight for seven days did not differ from those exposed to sunlight for 28 days, indicating that a full adaptation ocurred within this period. Higher wind speeds led to lower cluster temperatures and reduced sunburn severity. First evidence of a drought priming induced heat tolerance of grapevine berries was found, while adaptation had a more pronounced effect on the susceptibility to sunburn compared to water stress.